2011
DOI: 10.1073/pnas.1108436108
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of tryptophan to indole-3-acetic acid by TRYPTOPHAN AMINOTRANSFERASES OF ARABIDOPSIS and YUCCAs in Arabidopsis

Abstract: Auxin is an essential hormone, but its biosynthetic routes in plants have not been fully defined. In this paper, we show that the TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS (TAA) family of amino transferases converts tryptophan to indole-3-pyruvate (IPA) and that the YUCCA (YUC) family of flavin monooxygenases participates in converting IPA to indole-3-acetic acid, the main auxin in plants. Both the YUCs and the TAAs have been shown to play essential roles in auxin biosynthesis, but it has been suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
554
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(589 citation statements)
references
References 21 publications
16
554
0
3
Order By: Relevance
“…The deuterated 4-Cl-IAA was Figure 6. Proposed parallel IAA and 4-Cl-IAA biosynthetic pathways in pea seeds, based on this study and previous evidence (Manabe et al, 1999;Reinecke, 1999;Quittenden et al, 2009;Tivendale et al, 2010;Zhao, 2010;Mashiguchi et al, 2011;Stepanova et al, 2011;Won et al, 2011;Kriechbaumer et al, 2012). IAA does not become chlorinated, and Trp is a point of chlorination.…”
Section: Chemicalssupporting
confidence: 63%
See 3 more Smart Citations
“…The deuterated 4-Cl-IAA was Figure 6. Proposed parallel IAA and 4-Cl-IAA biosynthetic pathways in pea seeds, based on this study and previous evidence (Manabe et al, 1999;Reinecke, 1999;Quittenden et al, 2009;Tivendale et al, 2010;Zhao, 2010;Mashiguchi et al, 2011;Stepanova et al, 2011;Won et al, 2011;Kriechbaumer et al, 2012). IAA does not become chlorinated, and Trp is a point of chlorination.…”
Section: Chemicalssupporting
confidence: 63%
“…There is currently a renewed focus on auxin biosynthesis, due to reports that the YUC proteins do not operate in the tryptamine pathway (Tivendale et al, 2010) but rather the IPyA pathway Stepanova et al, 2011;Won et al, 2011;Kriechbaumer et al, 2012), as suggested previously by Strader and Bartel (2008). However, Mano and Nemoto (2012) recently noted that functional activity for Trp aminotransferases from the IPyA pathway has been demonstrated only for Arabidopsis genes and implied that the IPyA pathway might be restricted to the Brassicaceae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 175 K4-SDRGs that displayed a loss of H3K4me3 marks and decreased gene expression, 13 encoded YUCCA-and SAUR-like genes involved in auxin biosynthesis Stepanova et al, 2011;Won et al, 2011) and response, respectively (Spartz et al, 2012(Spartz et al, , 2014. Auxin synthesis sets in motion major changes in gene expression and physiology (Guilfoyle and Hagen, 2007), and the down-regulation of auxin synthesis and signaling can be considered a primary event in the progression of senescence.…”
Section: Discussionmentioning
confidence: 99%